2022
DOI: 10.1002/cphc.202200146
|View full text |Cite
|
Sign up to set email alerts
|

Strongly Bound π‐Hole Tetrel Bonded Complexes between H2SiO and Substituted Pyridines. Influence of Substituents

Abstract: Ab initio calculation at the MP2/aug-cc-pVTZ level has been performed on the π-hole based N … Si tetrel bonded complexes between substituted pyridines and H 2 SiO. The primary aim of the study is to find out the effect of substitution on the strength and nature of this tetrel bond, and its similarity/difference with the N … C tetrel bond. Correlation between the strength of the N … Si bond and several molecular properties of the Lewis acid (H 2 SiO) and base (pyridines) are explored. The properties of the tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 50 publications
3
19
0
Order By: Relevance
“…This strength extends also to bonding to π-holes generated on Si 63,64 when in a trivalent situation as in F 2 SiO 23 or H 2 SiO 65 where the N⋯Si interaction with substituted pyridines exceeds 30 kcal mol −1 and the distance between the two atoms is essentially equal to the sum of their covalent radii. Like the σ-hole bonds discussed here, there is a large deformation energy, roughly 8 kcal mol −1 in these cases.…”
Section: Discussionmentioning
confidence: 79%
“…This strength extends also to bonding to π-holes generated on Si 63,64 when in a trivalent situation as in F 2 SiO 23 or H 2 SiO 65 where the N⋯Si interaction with substituted pyridines exceeds 30 kcal mol −1 and the distance between the two atoms is essentially equal to the sum of their covalent radii. Like the σ-hole bonds discussed here, there is a large deformation energy, roughly 8 kcal mol −1 in these cases.…”
Section: Discussionmentioning
confidence: 79%
“…[28][29][30][31][32][33] This bond shares several common features with other π-hole based non-covalent interactions, especially the chalcogen and tetrel bonds. [34,35] A substantial charge transfer from the Lewis base to the vacant p orbitals of Be of the X 2 Be molecule is one of the significant characteristics of beryllium bonds. [30] Frontera et al with a Protein Data Base (PDB) search showed the experimental evidence of π-hole beryllium-bond in biological systems.…”
Section: Introductionmentioning
confidence: 99%
“…[33] Numerous experimental and theoretical studies have been carried out on beryllium bonds concerning its physical nature, cooperativity and its usefulness in molecular recognition and solid-state chemistry. [34][35][36] A considerable amount of efforts have also been devoted on the beryllium bonded complexes between nitrogen bases and BeX 2 molecule (X=H, F, Cl, OH). [37][38][39][40] Very often in crystal engineering, nitrogenbases like substituted bipyrdines, diazines and other substituted pyridine-based bases like acridine and 4-dimethylaminopyridine are being used as the constituent molecules (as Lewis bases) of non-covalently bonded cocrystals which finds its application in the field of optoelectronic materials.…”
Section: Introductionmentioning
confidence: 99%
“…In detail, the σ-hole was illustrated to be an electron-deficient site located opposite to the covalent bond. , Apparently, π-hole was announced to describe a perpendicular electron-deficient portion to a planar skeleton of a molecular system. Afterward, lone-pair (lp) hole was launched to be in the mirror to the lp position. Recently, radical (R • ) hole was found in an opposite direction to the single electron (R • ) . The electrophilic character of such holes enabled group IV–VIII elements to form spurious interactions with Lewis bases (LBs), dubbed as tetrel, pnicogen, chalcogen, halogen, and aerogen bonds, respectively.…”
Section: Introductionmentioning
confidence: 99%